2013
DOI: 10.3109/08880018.2012.762962
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Adipose-derived Mesenchymal Stem Cells Are Effective in the Prevention and Treatment of Doxorubicin Cardiotoxicity in Rats

Abstract: Anthracyclines can cause severe cardiac toxicity leading to heart failure. The aim of this study was to determine the effects of cardioprotective polyphenolic compound resveratrol (RES) and adipose-derived mesenchymal stem cells (ADMSCs) on cardiac tissue of rats treated with doxorubicin (DOX). Forty-two female and three male Wistar-Albino rats were included in the study. The study groups and the control groups were as follows: Group I: DOX; Group II: DOX + RES; Group III: DOX + ADMSCs; Group IV: DOX + RES + A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…The MSCs-treated group showed a significant increase of MVP, EDP, dP/dt max, and dP/dt min at the end of the 6th week; consistent with previous studies [Rota et al, 2007;Ammar et al, 2015]. General improvement of the left ventricular function after systemic administration of MSCs was also shown by Oliveira et al [2013] and Pinarli et al [2013]. MSCs-mediated cardiac repair and function saving effects include modulation of inflammation, promotion of angiogenesis and reducing cardiac fibrosis that is critical in improving the performance and the function of the affected heart [Loffredo et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The MSCs-treated group showed a significant increase of MVP, EDP, dP/dt max, and dP/dt min at the end of the 6th week; consistent with previous studies [Rota et al, 2007;Ammar et al, 2015]. General improvement of the left ventricular function after systemic administration of MSCs was also shown by Oliveira et al [2013] and Pinarli et al [2013]. MSCs-mediated cardiac repair and function saving effects include modulation of inflammation, promotion of angiogenesis and reducing cardiac fibrosis that is critical in improving the performance and the function of the affected heart [Loffredo et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with previous studies [Di et al, 2012;Mohammadi Gorji et al, 2012;Oliveira et al, 2013;Ammar et al, 2015], reflecting the beneficial effects of MSCs on DOX-induced cardiotoxicity and heart failure. Moreover, MSCstreated group, showed improved survival as reported by Di et al [2012] and Pinarli et al [2013]. This could be attributed to the capacity of MSCs to act as a trophic factor pool combating different degenerating and debilitating conditions [Wei et al, 2013].…”
Section: Discussionmentioning
confidence: 71%
“…Our results are consistent with the recent findings of Latorre et al who discovered that treatment with resveralogues reversed cellular senescence in human primary fibroblasts. Many other studies confirmed the beneficial effects of RES on MSC biology, mainly by enhancing their differentiation potential …”
Section: Discussionmentioning
confidence: 74%
“…Anthracycline‐induced cardiotoxicity is attributed mainly to free radical formation in the mitochondria resulting in apoptosis of cardiac cells; MSCs were able to improve histopathologic and functional features and result in improved cardiac function after doxorubicin treatment in animal models . Additionally, bmMSCs were shown to regenerate doxorubicin‐induced nephropathy by reducing glomerular inflammation and preserving podocyte viability .…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%